(untitled) (Arquivos em Odontologia, 2024)
In its 60th anniversary year, one of the oldest Brazilian scientific journals in Dentistry is undergoing a process of reinvention to fully realize its mission of promoting and disseminating intellectual production in the fields of health and education in Dentistry.